MOTIVASI WARGA DALAM PELAKSANAAN PROGRAM DEMPLOT URBAN FARMING DI KAWASAN KAMPUNG MARUNDA KECAMATAN CILINCING JAKARTA UTARA - Riesma Andiani; Harsoyo Harsoyo; Subejo Subejo (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2018)
Demplot urban farming program is a part of some activity series of MURIA (Marunda Urban Resilience in Action) focused on the effort to introduce urban farming to Marunda village residents in order to improve environment and economic aspect. The objectives of the study are to: 1) To analyze the motivation of Marunda village residents on demplot urban farming program implementation, 2) To identify affecting factors of the motivation of Marunda village residents on demplot urban farming program implementation. Analytical descriptive method was used as basic method. Sampling method of this study usedsimple random sampling with total respondents were 60 people residents of Marunda village who’s join on demplot urban farming program. Proportion statistical test and multiple linear regression analysis were applied for data analysis. Research results showed that Marunda vilage resident’s motivation toward implementation of demplot urban farming program reached level at 73,33%. Marunda vilage resident’s motivation was significantly affected by attitude, role of the supervisor, and availibility of infrastructures.